Asphalt rubber interlayer benefits on reflective crack retardation of flexible pavement overlays - Shatnawi, Shakir (2011)
This paper provides an overview of the asphalt rubber interlayer benefits on reflective crack retardation in flexible pavement preservation and rehabilitation strategies. These interlayers are known in California as asphalt rubber absorbing membrane interlayers (SAMI-R) or as asphalt rubber aggregate membrane interlayers (ARAM-I) chip seals. These interlayers have been used successfully as part of cape seals and as part of an overlay system. The paper focuses on the performance in terms of field project reviews, laboratory performance tests and finite element analysis. The paper concluded that SAMI-R are effective in minimizing reflective cracking distress and in extending pavement life.